2016
DOI: 10.1177/1536012115624920
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of New Tau PET-Tracer Candidates With [18F]T808 and [18F]T807

Abstract: Early clinical results of two tau tracers, [18F]T808 and [18F]T807, have recently been reported. In the present study, the biodistribution, radiometabolite quantification, and competition-binding studies were performed in order to acquire comparative preclinical data as well as to establish the value of T808 and T807 as benchmark compounds for assessment of binding affinities of eight new/other tau tracers. Biodistribution studies in mice showed high brain uptake and fast washout. In vivo radiometabolite analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 37 publications
(107 reference statements)
2
38
0
Order By: Relevance
“…The precursor for radiosynthesis of 18 F-AV1451 and the authentic reference material and the nonradioactive reference material for AV680 and AV45 were synthesized by Janssen Research and Development (Janssen Pharmaceutica NV, Beerse, Belgium) according to literature reports (13). All other chemicals and reagents were purchased from commercial sources and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The precursor for radiosynthesis of 18 F-AV1451 and the authentic reference material and the nonradioactive reference material for AV680 and AV45 were synthesized by Janssen Research and Development (Janssen Pharmaceutica NV, Beerse, Belgium) according to literature reports (13). All other chemicals and reagents were purchased from commercial sources and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…Data were acquired and analyzed using a GINA Star data acquisition system (Raytest). Quantification of radioactivity in samples of biodistribution and radiometabolite studies was performed according to a previously reported procedure (13). Quantitative data are expressed as mean 6 SD.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations